2x-93=33

Simple and best practice solution for 2x-93=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-93=33 equation:



2x-93=33
We move all terms to the left:
2x-93-(33)=0
We add all the numbers together, and all the variables
2x-126=0
We move all terms containing x to the left, all other terms to the right
2x=126
x=126/2
x=63

See similar equations:

| 12(x+9)-4=51 | | 5f-2f=12 | | 8(x-1)4=4(2x-3) | | (3x-1)(3x-1)+1=14x-2 | | 44+6y=2(4y+3)+2(2y+7) | | 2t+7=t+36 | | 3^x=35 | | 240x+0.25=180-0.40 | | 2t+7t=t+36 | | 19z+5=-14 | | 14+8=x+x | | 12x+8(x-2)=14 | | -4d+3-9d=-30 | | 3(2x+4)=-36 | | 6x/5=8x-4/3 | | 150-x-2x=12x | | .5q=0.25 | | 44+6y=4(y+3)+2(y+7) | | 3(7k+3)(7k-3)=0 | | (x+4)°+72°=180 | | -3(v+1)+7v=4(v+4)-5 | | 58=t-1 | | 5(x+2)+9(1/3x+5)+9=8x | | 35-5v=-7(-5-6v) | | 2.2-0.5(0.6x-1.8=) | | 2x+4x=2200 | | -12(x+4)=240= | | x/7+x/2=3/2 | | v/3+-6=-24 | | X=X+327+4+3*x | | 3x-2.6=x+82 | | x+3(x+7)=234 |

Equations solver categories